Analysis of Students' 4C Skills Based on Project Based Learning through Chemo Entrepreneurship Media - Fuldiaratman Fuldiaratman; Firdiawan Ekaputra (PT ARRUS Intelektual Indonesia, 2023)
This study aims to analyze students' 4C skills by applying a chemistry learning model assisted by chemo entrepreneurship media. 4C skills or 21st century skills include communication, collaboration, critical thinking, and creativity. The subjects of this study were students of the Jambi University Chemical Education Research Program in the psychology of learner development course class B in the 2023/2024 academic year. This research is a quasi-experimental research with a one-group pretest-posttest design. Data on 4C skills were collected using a questionnaire before and after the application of a project-based learning model supported by chemo entrepreneurship media. Data related to 4C skills were then tested using paired sample t-test. The significance test results with paired sample t-test showed a value of 0.00. These results are less than 0.05 so that this study shows the application of project-based learning models assisted by chemo enterpreneurship media.